A sub-minute CZE method to determine nitrate and nitrite in meat products: An alternative for routine analysis. (September 2016) - Della Betta, Fabiana; Pereira, Lais Morilla; Siqueira, Mariana Araújo; Valese, Andressa Camargo; Daguer, Heitor; Fett, Roseane; Vitali, Luciano; Costa, Ana Carolina Oliveira
Abstract: A sub-minute capillary zone electrophoresis (CZE) method was optimized and a simple sample preparation procedure based on the extraction of the analytes with water and sodium tetraborate was developed for the simultaneous determination of nitrate and nitrite levels in meat products. The background electrolyte (BGE) was composed of 20 mmol L − 1 perchloric acid and 65 mmol L − 1 β-alanine at pH 3.83. Thiocyanate was used as the internal standard. The proposed method was validated and the uncertainty estimated according to Eurachem guidelines. The run time was only 30 s, allowing analyzing more than 25 samples/h, the good analytical performance confirms the suitability of the method for the analysis of meat products. One sample presented residual nitrite levels above the limit established by MERCOSUL legislation (150 mg kg − 1 ). The use of a fast method in association with a simple sample preparation step means that this procedure represents a possible alternative to fulfill the demand for high throughput in routine laboratory analysis. Graphical abstract: Highlights: A sub-minute CZE was proposed to determine nitrate and nitrite in meat products. A simple and environmentally friendly sample preparation was developed. Full intra-laboratory validation and uncertainty measurement were performed according to Eurachem. The CZE method was applied to analyze several meat products. The method showed good analytical performance in the analysis of meat products.